Understanding crypto currencies, Bitcoins, blockchains (LiveLessons., 2018)
"The Understanding Crypto Currencies, Bitcoins, and Blockchains LiveLessons course provides more than 6 hours of detailed discussion introducing you to the world of Bitcoin and it's evolution. Aamir and Keith provide a historical foundation of money, currency, trade, banking, and the advent of digital currency. They use slides and lite board demonstrations to illustrate complex Bitcoin and Blockchain concepts, and walk you through some of the transactions needed to tap into the digital currency market. They discuss the pros and cons of decentralized banking and digital currency, including some of the large-scale cybercrime and money laundering cases affecting this new and vulnerable market, as well as some of the potential benefits in market and efficiency. They discuss some of the various types of cryptocurrencies, and what the future may hold for the market and Blockchain as a whole."--Resource description page